Measuring Achievement Striving via a Situational Judgment Test : The Value of Additional Context - Golubovich, Juliya; Lake, Christopher J.; Anguiano Carrasco, Cristina; Seybert, Jacob (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
The study extends personality and situational judgment test (SJT) research by using an SJT to measure achievement striving in a contextualized manner. Employed students responded to the achievement striving SJT, traditional personality scales, and workplace performance measures. The SJT was internally consistent, items loaded on a single factor, and scores converged with other measures of achievement striving. The SJT provided incremental criterion-related validity for the performance criteria beyond less-contextualized achievement striving measures. Findings suggest that achievement- related work scenarios may provide additional criterion-relevant information not captured by measures that are less contextualized.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Journal of work and organizational psychology, vol. 36, n. 2 (August 2020), P. 157-167.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Amplitud; Contextualización.; Esfuerzo hacia el logro; Fidelidad; Interaccionismo; Rasgos de personalidad; Tests de Juicio Situacional; Artículos electrónicos.